PARAMETER KEYAKINAN HAKIM DALAM MEMUTUS PERKARA PIDANA - Triantono, Triantono; Marizal, Muhammad (Justitia et Pax, 2021)
According to Article 183 of the Criminal Procedure Code, a judge may not impose a sentence on a person unless he has at least two valid evidence and he is convinced that a criminal act actually occurred and that the defendant was guilty of committing it. In this context there are at least two means of evidence and belief must be applied cumulatively based on the negative evidence theory (negative wettelijk bewijs theorie) adopted in Indonesia. The word two means of evidence refers to the parameter that there must be at least two pieces of evidence from the four pieces of evidence that have been determined limitatifly based on Article 184 of the Criminal Procedure Code, but the problem is that there is no clear measure (parameter) regarding the judge's conviction. The results of the study concluded that the judge's confidence parameters consisted of formal parameters and material parameters. Formal parameters are very much determined by formal evidence as stipulated in law and jurisprudence. Meanwhile, material actors have a freer character not only to see formal procedural facts but also to juridical, sociological, and philosophical aspects.